Is job polarization a recent phenomenon? Evidence from Sweden, 1950-2013, and a comparison to the United States - Magnus Gustavsson (Uppsala University, Department of Economics, 2017)
In this paper, I first show that Swedish job polarization is - contrary to common belief - a long-run phenomenon: the share of middle-wage jobs has declined relative to the highest- and lowest-paid jobs since at least the 1950s. Based on previous results for the US, I then demonstrate that the same major employment shifts across routine and nonroutine jobs drive long-run job polarization in both Sweden and the US. In particular, the shrinking manufacturing sector, with the subsequent decline of routine manual (blue-collar) jobs, stands out as the main explanation for why job polarization is a long-run phenomenon. However, consistent with the hypothesis of routine-biased technological change, both countries display across-the-board declines of routine jobs from around the 1980s, as well as polarizing employment patterns not only between but also within industries. But despite these trend breaks, Sweden actually experienced a stronger job-polarization process - a more pronounced hollowing out of the job-wage distribution - in the pre- than in the post 1980-era.
urn:nbn:se:uu:diva-334548
Keywords: J21; J23; N10; N30; O33; 330; Automation; Industrial Composition; Routine-Biased Technological Change; Routinization; Structural Change